Penanganan Bencana Hidrometeorologi melalui Bantuan Kemanusiaan bagi Korban Banjir Bandang Kabupaten Aceh Barat - Dwinta, Ade; Erliana, Hilma; Luthfi, Luthfi; Wulansari, Intan; Marlina, Lilis (-, 2026)
This community service activity was conducted as a response to the flash flood disaster that struck Woyla Barat District, Aceh Barat Regency, in 2025, which caused damage to settlements, disruption of socio-economic activities, and limited access to basic needs for the affected communities. This activity is considered important due to the high vulnerability of the area to hydrometeorological disasters and the need for active involvement of higher education institutions during the emergency response phase. The objective of the program was to support the fulfillment of basic needs for affected communities while strengthening the role of local institutions through a community-based approach. The method employed was a responsive and participatory approach, including coordination with partners, beneficiary data collection, humanitarian aid distribution, and brief community assistance. The results indicate that the aid was distributed appropriately, enhanced social solidarity, and reduced the economic burden on communities during the early post-disaster phase. This activity highlights the importance of collaboration between higher education institutions and local organizations in community-based disaster response.